Serious Play: Sir John Harington’s Material-Textual Errancy in Orlando Furioso in English Heroical Verse (1591) - Reid, Joshua (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2020)
Sir John Harington’s Orlando Furioso in English Heroical Verse (1591) is a significant example of material-textual Englishing: under the direction of Harington, his book’s emblematic title page, copperplate engravings, typography, mise-en-page, and commentary apparatus are all transmutations of the preeminent Italian editions of the sixteenth century, most notably Francesco de Franceschi’s lavish 1584 edition. This article traces how Harington cannily deploys his bibliographic code in metatextual and metavisual ways to call attention to how the material-textual manipulates the reader’s experience. In what could be called an act of early postmodern deconstruction, Harington playfully dismantles the edifying structures of pragmatic humanism in the same way that romance dissolves epic.